Innovative governance systems and green innovations of agriculture-related enterprises based on the approach of fuzzy-set qualitative comparative analysis - Bao, Huricha; Chen, Chibo; Liu, Yuemin (Frontiers in Environmental Science, 2022)
The green innovation (GI) of agriculture-related enterprises has been an important factor to the ecological and sustainable development of agriculture. This research integrates the eight elements of the internally and externally governing mechanisms in the innovative governance system (IGS), adopts the fuzzy-set qualitative comparative analysis (fsQCA) from the configuration perspective, taking the data of A-shares’ listed agricultural companies in Shanghai and Shenzhen stock markets from 2007 to 2019 as samples, and explores the configuration effects of highly green innovations (GIs) from the collaborative matching of various elements of the enterprises’ IGS. The research results showed that 1) a single element of this IGS was unable to become a requisite for agriculture-related enterprises to generate highly GIs, but government subsidies played a more universal role in such a process; 2) the “multiple synergies” of various elements in the enterprises’ IGS formed six different configurations to drive highly GIs, namely, three major models of internal and external supervision with an external incentive, internal supervision with internal and external incentives, and internal and external supervision with internal and external incentives; 3) there were five different paths for the IGS of agriculture-related enterprises to generate non-highly GIs, which were in asymmetry with the configuration paths to generate the highly GIs.